Clinical Relevance of Rehospitalizations for Unstable Angina and Unplanned Revascularization Following Acute Myocardial Infarction. Issue 8 (20th August 2016) - Shore, Supriya; Smolderen, Kim G.; Spertus, John A.; Kennedy, Kevin F.; Jones, Philip G.; Zhao, Zhenxiang; Wang, Tracy Y.; Arnold, Suzanne V.
Abstract : Background: Rehospitalizations following acute myocardial infarction for unplanned coronary revascularization and unstable angina (UA) are often included as parts of composite end points in clinical trials. Although clearly costly, the clinical relevance of these individual components has not been described. Methods and Results: Patients enrolled in a prospective, 24‐center, US acute myocardial infarction registry were followed for 1 year after an acute myocardial infarction for rehospitalizations, that were independently adjudicated by experienced cardiologists. Patients who did and did not experience UA or revascularization rehospitalization were propensity matched using greedy matching. Among 3283 patients with acute myocardial infarction who were included, mean age was 59 years, 33% were female, and 70% were white. Rehospitalization rates for UA and unplanned revascularization at 1 year were 5.0% and 4.1%, respectively. After propensity matching, we included 2433 patients in the UA rehospitalization group and 2410 in the unplanned revascularization group. Using weighted proportional hazards Cox regression, there was no significant association between a rehospitalization for UA and 5‐year all‐cause mortality (9.6% versus 13.8%; adjusted hazard ratio 0.87, 95% CI 0.60–1.16). Patients rehospitalized for unplanned revascularization had a lower 5‐year mortality risk (7.0% versus 15.1%; hazard ratio 0.68, 95% CI 0.50–0.92) compared with those without such rehospitalizations. Nevertheless, patients with UA and unplanned revascularization had a substantially greater hazard of subsequent rehospitalizations compared with patients without such events (UA: hazard ratio 4.36, 95% CI 3.48–5.47; revascularization: hazard ratio 4.38, 95% CI 3.53–5.44). Conclusions: Rehospitalizations for UA and unplanned revascularization in the year after an acute myocardial infarction are associated with higher risks of subsequent rehospitalizations but not with mortality.